Tindak Tutur Ekspresif dalam Web Series Progresnya Berapa Persen? dan Relevansinya terhadap Pembelajaran Cerita Fantasi di SMP - Chaterine Valentina Silalahi; Lazarus Linarto; Albertus Purwaka; Indra perdana; Petrus Poerwadi; Alifiah Nurachmana; Paul Diman; Patrisia Cuesdeyeni; Hana Pertiwi; Isti Rahayu (Universitas Palangka Raya, 2025)
The purpose of this study is to (1) describe the types of expressive speech acts carried out by the characters in the web series How Much Progress? (2) describe the function of expressive speech acts in the web series How Much Progress? and (3) describe its relevance to fantasy story learning in junior high schools. This study uses a qualitative method with the research subjects being the web series How Much Progress? and the form of data in the form of speech from the dialogue in the web series How Much Progress? In addition, the data collection procedure uses the listening and note-taking method. The data analysis used is the analysis of the content of speech in the web series How Much Progress? dialogue and the data validity checking technique carried out using triangulation and member check techniques. The results of this study indicate that (1) regarding its form, expressive speech acts contained in the web series How Much Progress? consist of 4 forms of speech, namely the type of direct literal speech act, the type of direct non-literal speech act, the type of indirect literal speech act, and the type of indirect non-literal speech act. (2) regarding the function of expressive speech acts in the web series How Much Progress? consists of 6 functions, namely thanking, apologizing, praising, complaining, sympathizing, and expressing anger. The results of the study are relevant to fantasy story learning in junior high schools, students can identify characters and characterizations in web series What is the percentage of progress?